Optimize thermal comfort of HDB buildings - Ong, Edmund Zhe Ming. (2013)
This purpose of this paper is to propose guidelines that optimize the thermal comfort of HDB buildings. The study involves understanding the air flow characteristics around buildings, how the air flow changes with different designs and how to determine an air flow profile that optimizes thermal comfort. Computational Fluid Dynamics (CFD) software Ansys Fluent v14.0 was used to build the geometries of different models and simulate three-dimensional air flow patterns around each building cluster. Firstly, a model is built with reference to Treelodge@Punggol. It is a cluster that is strategically orientated to face prevailing winds and its design promotes natural cross ventilation. The results from the case study helped determine important factors for subsequent models. The factors include gap size between individual buildings, offset distance between the two rows of buildings, and the angle of orientation towards prevailing winds. Thereafter, the models designed are classified into regular, staggered and angular patterns with varying gap distance throughout the cluster. Wind directions would then be set normal to the top of the enclosure boundary and the wind passing through passage gaps between buildings are analyzed. Other factors like length, width and height dimensions of individual buildings; distance between enclosure boundaries to buildings, the mesh settings, velocity inlet profile and the setup settings are kept constant. Results obtained showed that the staggered building model has relatively better air flow within the cluster itself out of the three models. However, its’ immediate downwind or wake region is relatively large and remains so despite any changes to the building gap distances. Any buildings located in the wake region would have prevailing winds blocked by the initial staggered building model and would not bode well in terms of thermal comfort for a large scale development project. The angular building model, in comparison, has slightly less air flow than the staggered model but yields a much smaller wake region. This wake region would also decrease in size with respect to an increase in building gap distance which may be a preferred choice. The results show the impact of certain features and may be useful in depicting the general layout of a building cluster, in terms of its surroundings, whether it is a single cluster surrounded by landed property, or a cluster in a densely built, high-rise estate. Further studies may draw upon the results and focus on more variation in the building gap distance, offset distances and the angle of orientation, or include other variables like the differences in building height.